2015
DOI: 10.1158/1541-7786.mcr-14-0570
|View full text |Cite
|
Sign up to set email alerts
|

Adapting a Drug Screening Platform to Discover Associations of Molecular Targeted Radiosensitizers with Genomic Biomarkers

Abstract: Large collections of annotated cancer cell lines are powerful tools for precisely matching targeted drugs with genomic alterations that can be tested as biomarkers in the clinic. Whether these screening platforms, which utilize short-term cell survival to assess drug responses, can be applied to precision radiation medicine is not established. To this end, 32 cancer cell lines were screened using 18 targeted therapeutic agents with known or putative radiosensitizing properties (227 combinations). The cell numb… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

5
3

Authors

Journals

citations
Cited by 35 publications
(57 citation statements)
references
References 45 publications
1
56
0
Order By: Relevance
“…Annotated NSCLC cell lines were originally obtained from the MGH/Sanger cancer cell line collection http://www.cancerrxgene.org/translation/CellLine in the time period 2009–10, with the exception of A549 cells which were purchased from ATCC, as described in detail in previous publications (27, 29). Cell cultures were passaged for < 3 months after thawing an individual frozen vial.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Annotated NSCLC cell lines were originally obtained from the MGH/Sanger cancer cell line collection http://www.cancerrxgene.org/translation/CellLine in the time period 2009–10, with the exception of A549 cells which were purchased from ATCC, as described in detail in previous publications (27, 29). Cell cultures were passaged for < 3 months after thawing an individual frozen vial.…”
Section: Methodsmentioning
confidence: 99%
“…The identity of the cell lines had been tested as described using a set of 16 short tandem repeats (STR) (AmpFLSTR Identifier KIT, ABI). In addition, single nucleotide polymorphism (SNP) profiles based on a panel of 63 SNPs assayed using the Sequenom Genetic Analyzer was used for in-house identity checking whenever a cell line was propagated and confirmed uniqueness of cell lines for the ones without available STR (27, 29). On some cell lines additional authentication was performed by Bio-Synthesis, Inc (Lewisville, TX).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Liu et al reported an automated high-throughput (HTS) drug-screening platform (Figure 3) (27) based on short-term cell proliferation/survival assays (3-5 days incubation). These assays were used to derive a Short-term Radiosensitization Factor at 2 Gy (SRF 2Gy ), which correlates with standard Dose Enhancement Factors (DEF) derived from clonogenic survival assays using radiation doses up to 8 Gy.…”
Section: Focus Areas: Preclinical Radiobiological Assaysmentioning
confidence: 99%
“…Right panel, fraction of head and neck squamous cell cancer (HNSCC) cells with at least 20 γ-H2AX foci after treatment with IR with or without 17-AAG (Liu et al, unpublished). D) Radiosensitization factor for 2 Gy IR +/− 17-AAG using a previous IR/drug screening approach 129 . E) Representative images illustrating the persistence of 53BP1 foci following ex-vivo irradiation of tumor tissues from a bladder cancer patient.…”
Section: Figurementioning
confidence: 99%